A Comparative Study about Accuracy Levels of Resistance Temperature Detectors RTDs Composed of Platinum, Copper, and Nickel - Kako, Salim (Al-Nahrain Journal for Engineering Sciences, 2023)
Platinum, copper, and nickel were founded the best metals used in resistance temperature detectors RTDs. They commonly used in laboratory and industrial applications because they provide accurate and reliable measurements in a wide temperature range from (- 200 to 850 °C).  They have high conductivity, sensitivity, and hardness to resist strain shock, pressure, and vibration.The accuracy level of them depends on reliability, stability, repeatability, linearity, and response to time. This study aims to determine and compare the accuracy of these three metals in regarding to their features which include stability, repeatability, and response time. The study has gathered and analyzed the data of these suitable and precise metals and compared with each other.The results showed that platinum is widely needed for RTDs due to its precision, stability, higher accuracy, and linearity output, while copper and nickel are not stable or repeatable as platinum. It was indicated that temperature coefficient of resistance TCR for nickel is bigger and for copper is medium, but for platinum is lower.